The Effect of Company Risk and Company Complexity on Audit Fees with Moderation of Dividend Payment Policy : Empirical Study of Non-Financial Companies Listed on The BEI IN 2020 - 2022) - Gymnastiar, Danar; Muhsin, Muhsin; Desyana, Gita (Jurnal Indonesia Sosial Sains, 2024)
This study aims to determine: (1) The effect of company risk on audit fee, (2) The effect of company complexity on audit fee, (3) The effect of company risk on audit fees moderated by dividend payment policy, (4) The effect of company complexity on audit fees moderated by dividend payment policy. Population in this research ar e nonfinancial companies listed in Indonesia Stock Exchange (IDX) in 2020 – 2022. The sample is determined based on Stratified Random Sampling method with a total sample of 10 companiees. The data used in this research is secondary data. The technique of collecting data by the method of documentation at www.idx.com and the official website of each company. The analytical method used is multiple regression analysis. The result showed that: (1) Company risk influence a significant positive on audit fee, (2) Company complexity no significant effect on on audit fee, (3) Company risk no significant effect on audit fees moderated by dividend payment policy (3), and (4) Company complexity no significant effect on audit fees moderated by dividend payment policy.